MULTISECTORAL PARTNERSHIP THROUGH INTERACTIVE GOVERNANCE IN PREVENTING CHILD MARRIAGE IN PONOROGO REGENCY - Asmorowati, Sulikah; Anggika, Saskia Intandivanty Kamalia; Haya, Farah; Irianto, Jusuf; Widodo, Suko; Amalia, Yuni Sari; Azzahra, Adisty Nazwa Salshabila; Satryanto, Muhammad Ditya (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2026)
Child marriage is a complex issue with multidimensional impacts on the quality of life of children and adolescents, especially girls. Ponorogo Regency ranks relatively high in the number of marriage dispensation requests, particularly in Ngrayun District. This community engagement program aims to build a multisectoral partnership based on interactive governance to address the phenomenon of child marriage through youth education, community empowerment, and cross-sector stakeholder collaboration. The methods employed include English language training for adolescent girls, public outreach sessions, focus group discussions, and creative digital campaigns. The results of the program indicate an increase in participants’ understanding of the issue of early marriage and the importance of education, as well as the emergence of joint initiatives among stakeholders to continue advocacy efforts. This activity contributes to the achievement of the Sustainable Development Goals (SDGs), particularly in the areas of quality education, gender equality, and strong institutions.